Interview with Zaleha Kamaruddin (American Journal of Islam and Society, 2012)
In Southeast Asia and elsewhere in the Muslim world, academicinstitutions – particularly in the humanities and social sciences –often ignore the potential leadership role of women. This is especiallyevident in Islamic studies, where women play a minor rolein research, teaching, and course management. Generally speakingunlike in the Middle East, many public and private SoutheastAsian schools of higher learning, as well as “Islamic” schools,feature female Muslim scholars in their administrational structures.Indonesia boasts several woman serving as leaders in Islamiceducational organizations, and Masnon Ibrahim is thecurrent rector of Brunei’s Seri Begawan Religious Teachers UniversityCollege. On the international level, Zaleha Kamaruddin,the recently appointed rector of the International Islamic UniversityMalaysia (IIUM), remains the world’s first and only femalerector of an Islamic institution of higher learning.This short article seeks to address her feelings, style, and role, aswell the challenges in managing an international Islamic institution.It is based on her written answers to written questions, a recentunstructured interview, and personal contact gained whileworking together as administrators at IIUM during the 1990s.